The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adfm.202210551
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Cooling Strategy for Synergistic Control of CuZn and SnZn Defects Enabling 12.87% Efficiency (Ag,Cu)2ZnSn(S,Se)4 Solar Cells

Abstract: Abundant intrinsic defects and defect clusters in Cu 2 ZnSn(S,Se) 4 (CZTSSe) solar cells lead to severe nonradiative recombination and limited photoelectric performance. Therefore, developing effective method to suppress the detrimental defects is the key to achieve high-efficiency solar cell. Herein, a convenient two-step cooling strategy in selenization process is reported to suppress the Cu Zn and Sn Zn defects and defect clusters synergistically. The results show that rapid cooling during section from sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…The photoluminescence (PL) spectrum measured at 137 K shows a main peak centered at 1.090 eV (black line in the inset of Figure b), which is only 5 meV lower than the band gap obtained from EQE. Wu et al reported a decrease of the difference between the PL emission and the optical band gap from 20 to 2 meV by developing a two-step cooling strategy during selenization to suppress the defect states . The energy difference between the PL emission and the optical band gap in our finding is quite small, suggesting that there is a low band tail state density in the inkjet-printed CZTSSe absorber.…”
mentioning
confidence: 41%
See 1 more Smart Citation
“…The photoluminescence (PL) spectrum measured at 137 K shows a main peak centered at 1.090 eV (black line in the inset of Figure b), which is only 5 meV lower than the band gap obtained from EQE. Wu et al reported a decrease of the difference between the PL emission and the optical band gap from 20 to 2 meV by developing a two-step cooling strategy during selenization to suppress the defect states . The energy difference between the PL emission and the optical band gap in our finding is quite small, suggesting that there is a low band tail state density in the inkjet-printed CZTSSe absorber.…”
mentioning
confidence: 41%
“…Wu et al reported a decrease of the difference between the PL emission and the optical band gap from 20 to 2 meV by developing a two-step cooling strategy during selenization to suppress the defect states. 30 The energy difference between the PL emission and the optical band gap in our finding is quite small, suggesting that there is a low band tail state density in the inkjet-printed CZTSSe absorber. In summary, we demonstrate that compact and crack-free CZTSSe thin films with high crystallinity and a low band tail state density can be achieved by inkjet printing of the preoptimized precursor ink under ambient condition.…”
mentioning
confidence: 47%
“…140 In 2022, an efficiency of 12.87% was achieved using a two-step cooling strategy, which can suppress the Cu Zn and Sn Zn defects and defect clusters synergistically. 141…”
Section: Ethylene Glycol Methyl Ether-based Precursor Solution Method...mentioning
confidence: 99%
“…140 In 2022, an efficiency of 12.87% was achieved using a two-step cooling strategy, which can suppress the Cu Zn and Sn Zn defects and defect clusters synergistically. 141 Unlike amine-thiol, DMSO and other solvents, the fabrication of CZTSSe solars by EGME solvent is not only insensitive to oxygen and water in the air but also does not show decomposition or uneven morphology. Moreover, the precursor solution configuration process, including the spin coating process and annealing process by this solvent system, can be operated in the air.…”
Section: Extrinsic Doping Of Egme-based Routesmentioning
confidence: 99%
“…In the current research stage, greater focus has been paid to the CZTSSe absorber layer itself. Researchers have continuously explored to improve the CZTSSe crystal quality through bulk phase regulation, , element doping, , selenization/sulfurization modification, , solvent engineering, , and so on. Over 14% efficiency has been achieved for kesterite solar cells by regulating the phase evolution kinetics of Ag-alloyed CZTSSe in a positive pressure .…”
mentioning
confidence: 99%